The Canadian Childhood Nephrotic Syndrome (CHILDNEPH) Project: Overview of Design and Methods. Issue 1 (22nd July 2014) - Samuel, Susan; Scott, Shannon; Morgan, Catherine; Dart, Allison; Mammen, Cherry; Parekh, Rulan; Nettel-Aguirre, Alberto; Eddy, Allison; Flynn, Rachel; Pinsk, Maury; Wade, Andrew; Arora, Steven; et al.
Background: Nephrotic syndrome is a commonly acquired kidney disease in children that causes significant morbidity due to recurrent episodes of heavy proteinuria. The management of childhood nephrotic syndrome is known to be highly variable among physicians and care centres. Objectives: The primary objective of the study is to determine centre-, physician-, and patient-level characteristics associated with steroid exposure and length of steroid treatment. We will also determine the association of dose and duration of steroid treatment and time to first relapse as a secondary aim. An embedded qualitative study utilizing focus groups with health care providers will enrich the quantitative results by providing an understanding of the attitudes, beliefs and local contextual factors driving variation in care. Design: Mixed-methods study; prospective observational cohort (quantitative component), with additional semi-structured focus groups of healthcare professionals (qualitative component). Setting: National study, comprised of all 13 Canadian pediatric nephrology clinics. Patients: 400 patients under 18 years of age to be recruited over 2.5 years. Measurements: Steroid doses for all episodes (first presentation, first and subsequent relapses) tracked over course of the study. Physician and centre-level characteristics catalogued, with reasons for treatment preferences documented during focus groups. Methods: All patients tracked prospectively over the course of the study, with data comprising a prospective registry. One focus group at each site to enrich understanding of variation in care. Limitations: Contamination of treatment protocols between physicians may occur as a result of concurrent focus groups. Conclusions: Quantitative and qualitative results will be integrated at end of study and will collectively inform strategies for the development and implementation of standardized evidence-based protocols across centres.